Lipoma of Corpus Callosum - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A lipoma of the corpus callosum diagnosed by CT at 7 mos and mistaken for hemorrhage in a premature infant is reported from the Medical College of Pennsylvania, Philadelphia, PA.